Survey Of Socio-Demographic, Behavioral, and Clinical Factors Associated with Stroke in The Elderly in Indonesia - Nadia Rahmi Amelia Pratiwi; Yuni Asri; Rif'atul Fani; Dion Kunto Adi Patria (Care : Jurnal Ilmiah Ilmu Kesehatan, 2026)
Stroke is the leading cause of death and disability throughout the world, with a higher burden in low- and middle-income countries, including Indonesia. As the elderly population grows, identifying factors linked to stroke is essential for prevention and policy-making. This study aims to examine the association between sociodemographic, behavioral, and clinical factors and stroke among Indonesians aged ? 60 years using data from the 2023 Indonesian Health Survey (Survei Kesehatan Indonesia/SKI). This study employed a cross-sectional design using secondary data from a nationally representative survey. A total of 97,339 older adults were included in the analysis. Stroke status was based on self-reported physician-diagnosed status. Independent variables included age, sex, education, marital status, employment, residence, hypertension, heart disease, smoking, and alcohol consumption. Data were analyzed using complex survey analysis with sampling weights, utilizing descriptive statistics and Chi-square tests to examine associations between variables. Analyses were conducted using IBM SPSS Statistics version 27.0.1, adjusting stratification and clustering in the survey design. The prevalence of stroke was 3.2%. Significant associations were found between stroke and age, gender, education, occupation, place of residence, hypertension, heart disease, smoking habits, and alcohol use (all p0.05). Stroke was more common among individuals with hypertension, heart disease, lower educational attainment, those who were unemployed, and those living in urban areas. Stroke in older Indonesians is strongly influenced by modifiable factors, particularly hypertension and lifestyle behaviors. Targeted prevention, early detection, and lifestyle interventions are critical to mitigating the stroke burden in Indonesia’s aging population.